A traditional protestant church experiencing substantial membership decline: an organizational strength analysis and observations to attend or leave the institution. Issue 3 (3rd April 2020) - Fowler, David; Musgrave, Jon; Musgrave, Jill
Abstract : Purpose: This organizational climate empirical case study involves a religious organization in the United States of America, which has experienced a substantial decline in membership and weekly service participation numbers over the previous five years. The purpose of this qualitative case study is to reveal motivating factors that drive parishioners to leave or stay within a traditional protestant congregation and to uncover the strengths and weaknesses within the organization. Design/methodology/approach: The methodology behind the study considers personal observation by the author and engages current and former members of the organization as well as front-line employees and senior leadership. Qualitative essays were completed through Qualtrics by participants and analyzed with the use of MAXQDA software for thematic frequency and organization. Findings: During analysis, correlations were found to exist between the church's membership decline and ineffectiveness of senior leadership. Also, it is quite evident that the church's strengths were found in the quality of its members and the relationships they developed. This was found to be a significant motivation to stay within the organization. Originality/value: The study provides value to practitioners within organizational development fields. Usage of this knowledge could assist in providing insights into possible reasons why religious organizations falter under ineffective leadership, which in turn could provide opportunities to implement improvements based on discoveries.